EXPLORING CHILDREN'S IDEAS ABOUT SHADOW FORMATION (Heritage, 2024)
Preschool children have difficulty in explaining the phenomenon of shadow formation and the complexity of that phenomenon. In that respect,  the research goal  is to perceive the preschool children’s ideas about shadow formation based on drawings. The sample consisted of children from two educational groups, a total of 44 children, from the Preschool institution "Naša mladost" in Lapovo. A descriptive method and a technique of content analysis were applied, whereby pre-set categories were used: the presence of three entities needed to represent the phenomenon of shadow formation, the characteristics of the shadow, the relationship between the object, the shadow and the light source, and the nature of the light. The children mainly depicted shadow formation  using three entities (a light source, an object and a shadow) in different relationships. The shadow was often presented as a contour, using different colours and with unnecessary details. Children most often emphasized the importance of the sun for the formation of shadows. The research provided pre-school teachers and other interested parties with a tool for perceiving, interpreting and monitoring children's ideas as a basis for supporting the research of natural phenomena with children.
Keywords: pre-school children, children's drawings, shadow formation